(untitled) (Applied Biological Research, 2013)
Seed selenium (Se) concentrations of 22 genotypes (21 cultivars and one local check) of lentil (Lens culinaris Medik.), grown in different parts of West Bengal (India) including arsenic-affected areas, were estimated. Se content varied significantly in genotypes with highest (167 µg Se kg-1) and lowest (9 µg Se kg-1) content in cv. ‘Pusa 4’ and ‘VL Massor 44’, respectively. The 9 genotypes grown in arsenic-prone areas showed deficient Se levels. However, ‘Pusa 1’, ‘Pusa 6’, ‘JLS 1’, ‘Sehore 74-3’, ‘VL Masoor 44’ and ‘VL Masoor 103’ exhibited increased Se levels when grown outside the As-contaminated zones, indicating possible inhibition of Se uptake by As. Marginal variations in Se content in genotypes ‘B 17’, ‘PL 406’ and ‘S 256’ between As-contaminated and non-contaminated areas suggested genotype-dependent accumulation of Se.